Health workers contaminated with SARS-CoV-2 during their assistance functions in a hospital institution - Eduardo Robert Sánchez; Omara Mercedes Cardona Sanchez; Lisbet Estrada Ladoy (Medisan, 2022)
Introduction: The preservation of health professionals is always high-priority, especially in epidemic situations.